Pendampingan Latihan Range Of Motion (ROM) Pada Penderita Stroke - Sri Sudarsih; Windu Santoso (Universitas Mathla'ul Anwar Banten, 2022)
RANGE OF MOTION (ROM) EXERCISE ASSISTANCE IN STROKE PATIENTS. Stroke is the second leading cause of death and the third leading cause of disability in the world after heart disease and cancer in both developed and developing countries. Stroke occurs suddenly and causes symptoms, including paralysis of the face or limbs, speech is not fluent, speech is not clear (pelo), changes in consciousness, visual disturbances, and others. Stroke sufferers who experience disorders of the extremities require improvement of extremity motor skills through rehabilitation programs, one of which is range of motion (ROM) exercises. This community service activity is carried out through mentoring range of motion (ROM) exercises for stroke patients. ROM exercises are given using a cylindrical grip or a cylindrical tool made of wood. This tool is used by stroke patients for grasping exercises. When giving ROM exercises, stroke patients are accompanied by their families because this ROM exercise is not only done once but is carried out for 1 week with a frequency of 2 times a day (morning and evening) so it is hoped that there will be support from the family in helping stroke sufferers do this exercise. The results of community service activities showed that stroke patients experienced changes or increased muscle strength scales. Finger muscle strength can be increased by using cylindrical grip range of motion exercises. Stroke sufferers need to learn and apply ROM exercises in an effort to increase the scale of muscle strength.